Photo-patterning PEG-based hydrogels for neuronal engineering. (November 2015) - Berkovitch, Yulia; Yelin, Dvir; Seliktar, Dror
Graphical abstract: Highlights: UV laser energy controls dimensions of micro-channels in PEG-protein hydrogels. Directional neuron outgrowth in hydrogels is related to micro-channel dimensions. Signaling from ECM proteins influences neuronal outgrowth in micro-channels. PEG-fibrinogen hydrogels elicit a robust neuronal outgrowth into micro-channels. Abstract: We report on a photo-patterning technique that is applied to semitransparent three-dimensional (3D) hydrogel biomaterials for neuronal engineering. Microscopic patterns were laser-ablated into hydrogels made from polyethylene glycol conjugated extracellular matrix proteins, including fibrinogen, gelatin and albumin. The synthetic polymer provides a cross-linked network with transparency and physical properties that are suitable for photoablation, whereas the protein constituents provide the unique extracellular environment for neuronal cell morphogenesis. A dorsal root ganglion (DRG) assay was used to investigate how physical and biochemical attributes of the microchannels govern the directional outgrowth of neurites in the 3D patterned biomaterials. We specifically characterized the effects of microchannel diameter and protein constituents on the neurite extensions and glial cell migration. We found that the energy of the laser beam ablation can be used in order to control the dimensions of the channels and the subsequent outgrowth of neuronal cells into them. The biomolecular signaling from the fibrinogen backbone of the hydrogel had a similarly pronounced effect on neuronal outgrowth into the microchannels. These results indicated that trophic and topographical cues are essential in the design of neural engineering matrices that can be used for in vivo axonal regeneration or for basic neuronal morphogenesis research.